2019
DOI: 10.1177/0956247819886229
|View full text |Cite
|
Sign up to set email alerts
|

Struggles to remain in Kigali’s “unplanned” settlements: the case of Bannyahe

Abstract: Examining the precarious status of informal settlements in Kigali at a time of large-scale planning-induced expropriation, this article considers urban contestation in the context of the city’s changing spatial-legal regime. We analyse the case of one informal settlement’s expropriation and relocation – the settlement of Bannyahe – and the contestation that has ensued as resident property owners take the District of Gasabo to court. Through interviews with settlement residents, we follow the fates of these dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
(17 reference statements)
0
12
0
Order By: Relevance
“…Under the latter option, the affected people are relocated to another site. These urban redevelopment-induced resettlement projects in Kigali are currently being challenged by strong resistance from affected slum dwellers [70].…”
Section: Research Contextmentioning
confidence: 99%
“…Under the latter option, the affected people are relocated to another site. These urban redevelopment-induced resettlement projects in Kigali are currently being challenged by strong resistance from affected slum dwellers [70].…”
Section: Research Contextmentioning
confidence: 99%
“…Here, the central prison as the nodal point of colonial town planning (similar in some ways to 'prison towns' that are present in continental Europe and parts of the Eastern United States), was noticeably removed or functionally reorganized confluent with the advent of city masterplanning, and running in tandem with concerns over overcrowding and prison safety. My interviews and studies in the disappearing informal areas of the capital (Kimisagara, Kangondo and Kibiraro (also called Bannyahe), Gitega, and older built areas of Nyamirambo and Muhima) showed that masterplanning processes lacked wide participation amongst and accountability to low-income residents of the capital (Esmail and Corburn, 2020). The city was becoming a clean panopticon of restricted urban movement, negatively affecting the lives and livelihoods of many of its low-income residents.…”
Section: Methodsmentioning
confidence: 99%
“… 6. Esmail, Shakirah and Jason Corburn (2020), “Struggles to remain in Kigali’s “unplanned” settlements: the case of Bannyahe”, Environment and Urbanization Vol 32, No 1, pages 19–36. …”
mentioning
confidence: 99%